Controle de tensão e reativos em redes de distribuição de energia elétrica - Quijano Rodezno, Darwin Alexis [UNESP] (2014)
A new approach for the integrated Volt-Var control (IVVC) for medium voltage distribution networks operation is proposed here, seeking to explore the problem of energy savings and peak demand relief through the voltage reduction procedure called Conservation Voltage Reduction (CVR). Wide applications of CVR can provide significant benefits on technical, economic and environmental terms. However, in some cases, due to unexpected variation, significant voltage deviations may appear and cause undesirable voltage levels. Therefore, this paper seeks to mitigate the problem of voltage reduction application via multiobjective optimization. The proposal presented here is for the operation phase, taking into account the active power intake reduction and the voltage deviation, with a strategy based on a day ahead load forecast and considering the presence of transformers with On Load Tap Changer (OLTC), automatic voltage regulators, capacitor banks and distributed generation,. Therefore the result is a set of non-dominated optimal solutions (Pareto front), and the decision maker may decide when, where and how to apply them to meet different goals